Delayed Presentation of Lumbosacral Myelomeningocele with Tethered Cord Syndrome: Endogenous Tissue Expansion Enabling Primary Closure Without Flap Reconstruction - Hanifah Hasan; Imam Hidayat (Open Access Indonesian Journal of Medical Reviews, 2026)
Myelomeningocele (MMC) represents the most common open neural tube defect, typically presenting at birth or within the neonatal period. Delayed presentation beyond infancy in resource-limited settings remains exceptionally rare and poses unique surgical challenges, particularly regarding soft-tissue reconstruction and prevention of cerebrospinal fluid (CSF) leakage. This case highlights an unusual 4-year delayed presentation with progressive neurological deterioration including tethered cord syndrome and severe functional impairment requiring comprehensive multidisciplinary intervention. A 4-year-old male from rural Banda Aceh presented with a massive lumbosacral myelomeningocele, significant developmental delay, progressive lower extremity paresis (strength 2/5 bilaterally), and documented tethered spinal cord at L4. The patient demonstrated profound motor and sensory deficits with absent deep tendon reflexes and saddle distribution hypoesthesia. Neurosurgical intervention involved careful meningeal sac dissection, separation of functional from nonfunctional neural tissue, adhesiolysis, filum terminale sectioning, neural placode tubularization, and watertight dural closure. Remarkably, the chronic CSF accumulation had functioned as an endogenous tissue expander, providing sufficient skin laxity to enable primary midline closure without requiring flap reconstruction. Early postoperative assessment demonstrated neurological stabilization with subtle functional improvement and complete wound healing without complications. In conclusion, this case demonstrates the importance of multidisciplinary management in delayed neural tube defect presentation and introduces the concept of endogenous tissue expansion via chronic CSF accumulation as a novel biomechanical phenomenon enabling simplified soft-tissue reconstruction. Primary closure without flap reconstruction successfully prevented CSF leakage while preserving neurological stability in the postoperative period. Recognition of such mechanisms may inform surgical strategy in resource-limited settings where complex reconstructive options remain unavailable. The case highlights that even delayed presentations warrant aggressive surgical intervention when specialized expertise becomes available.